Evaluation of fibrinogen concentrates and prothrombin complex concentrates on coagulation changes in a hypothermic in vitro model using thromboelastometry and thromboelastography. (September 2015) - Durila, Miroslav; Lukáš, Pavel; Astraverkhava, Marta; Vymazal, Tomáš
Abstract Background. Hypothermic coagulopathy is very challenging in bleeding trauma patients. Therefore, we decided to evaluate the efficacy of fibrinogen and prothrombin complex in 30°C hypothermia in vitro to investigate if higher levels of fibrinogen and prothrombin complex concentrate can compensate for the hypothermic effect on coagulation as measured by thromboelastometry/thromboelastography. Methods. Blood samples were obtained from 12 healthy volunteers (six men and six women) in our study. Measurements were performed at 37°C and 30°C simultaneously, then at 30°C with adding fibrinogen and prothrombin complex and in the last step samples with added coagulation factors were warmed back to 37°C. Results. We found that 30°C hypothermic coagulopathy can be detected both by thromboelastometry and thromboelastography. Hypothermic coagulopathy can be restored by fibrinogen to the point where the results do not significantly differ from 37°C values (p > 0.05). After warming the sample with fibrinogen to 37°C, the thrombodynamic potential index was not significantly different from baseline (p > 0.05), although there was a trend to prothrombotic status. The addition of prothrombin complex concentrate to 30°C hypothermic sample was not able to correct hypothermic coagulopathy in vitro. Conclusions. Coagulopathy caused by the 30°C hypothermia in vitro model can be corrected by fibrinogen concentrate compared to prothrombin complex concentrate. In spite of a tendency to prothrombotic status, this was not significant with the use of the recommended dose of fibrinogen even after warming the blood to 37°C. However, measurement performed at 37°C seems to be safer than at 30°C.